2020
DOI: 10.1007/s10882-020-09768-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Brief Home-Based Intervention on Families with a Child with Autism Spectrum Disorder

Abstract: A brief intervention is described and evaluated that aimed to build and strengthen relationships for families of children diagnosed with ASD aged 12 and under. A particular focus was on socially disadvantaged parents. Parents were offered around five home visits which took place on weekdays during working hours; each lasting around 90 min. They were given individualised practical tools and support to manage their children’s behaviours alongside providing a listening ear to parents’ concerns. In all, 456 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This finding illustrates that the family would prefer to have agency and to control their own schedule at home [ 24 , 46 ] rather than to depend on healthcare providers [ 47 49 ]. Studies on CSHCN including conditions such as asthma, autism spectrum disorder, and diabetes have found that using a home-based intervention, not only improved child health and quality of life, but also relieved psychological distress within the family [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding illustrates that the family would prefer to have agency and to control their own schedule at home [ 24 , 46 ] rather than to depend on healthcare providers [ 47 49 ]. Studies on CSHCN including conditions such as asthma, autism spectrum disorder, and diabetes have found that using a home-based intervention, not only improved child health and quality of life, but also relieved psychological distress within the family [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some Southeast Asian countries, including Thailand, have launched universal coverage policies for a decade. Nevertheless, accessibility and quality of care have been identified as challenges in prior studies [ 28 , 29 , 49 , 50 ]. Due to geographical challenges, some health services and facilities were not available to the families in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also supports need to be provided to family caregivers to help build their coping strategies and enhance their emotional well-being. In Ireland, as in many other countries, such family-centred resources are not widely available and rarely on a preventative basis at a younger age [24]. Rather health and social services are focused on managing adolescents in crisis when higher levels of support are needed over longer periods with consequently greater costs.…”
Section: Discussionmentioning
confidence: 99%
“…During the recent COVID-19 pandemic, there was a trend in the use of telehealth to deliver services for young children with ASD and their families, such as social communication interventions ( Simacek et al, 2021 ), diagnostic assessments ( Gibbs et al, 2021 ), early interventions ( Pickard et al, 2016 ; Mullan et al, 2021 ), and ABA related services ( Ferguson et al, 2019 ). Therefore, we developed a culturally adapted group-based parent coaching intervention based on the P-ESDM.…”
Section: Introductionmentioning
confidence: 99%